Designing an A+ LED solar simulator: spectrum optimization and its impact on silicon solar cells - Boonmee, Chaiyant; Sritanauthaikorn, Patcharanan; Chudjuarjeen, Saichol; Kiatsookkanatorn, Paiboon; Wannakam, Khanittha; Homjan, Jeerawan; Sukthang, Kreeta; Suksing, Panet; Watjanatepin, Napat (Institute of Advanced Engineering and Science, 2025)
The development of light-emitting diode (LED)-based solar simulators that comply with the updated IEC 60904-9:2020 standard, particularly achieving a Class A+ irradiance spectrum, remains a significant challenge. This necessitates careful consideration of two key spectral quality indicators: spectral deviation (SPD) and spectral coverage (SPC). This study proposes a method to achieve a Class A+ solar simulator spectrum using a minimal number of LED types while optimizing SPD and SPC. It also examines the influence of SPD and SPC on the photogenerated current density (Jph) and short-circuit current density (Jsc) of crystalline silicon and multi-crystalline silicon solar cells. By selectively adding ultraviolet (UV) and near-infrared (NIR) LEDs to the original six-type LED configuration, the simulator’s spectral performance was enhanced to more closely align with the AM1.5G standard. The configuration incorporating both UV and NIR LEDs demonstrated the highest performance. It achieved an SPC of 97.521% and the lowest SPD at 26.088%. Simulation results confirmed that higher SPC and lower SPD values contribute to reduced errors in the calculated Jsc and Jph for both crystalline silicon (c-Si) and multi-crystalline silicon (mc-Si) solar cells. These findings highlight the importance of well-balanced spectral design and demonstrate that accurate spectral simulation is achievable using only essential LED wavelengths.